Application of six sigma philosophy for quality management system in construction - Ramli, Mohamad Ali (2010)
Quality performance and the client satisfactory is never ending topic to discuss. This study investigates the potential of Six Sigma application in construction industry as a quality management tools. The focus on the customer needs becomes the top priority and any improvement is guided by their impact on customer satisfaction and value. Quality management is part of critical factor applied in planning, organizing and managing projects to ensure the success of completion within project goals and objectives. On the other hand, Six Sigma is a statistical based process improvement methodology and risk management tool that helps in minimizing errors and risk, reducing cost, improving workflow and increasing customer satisfaction. The aim of this study is to evaluate the potential application of Six Sigma in quality control system for construction. The methodology used included data collection through literature review, interviews with expert panel in construction industry as well as the Six Sigma’s specialist, questionnaire survey, case study report, internet forum. The findings show that the Six Sigma applications can be implemented in construction industry. The benefits and the limitations of Six Sigma are also derived from the study. Among the benefits that the construction industry can benefit from Six Sigma application are: the influence of the final output of the businesess; improve quality of works; reduce defects; improve customer satisfaction; reduce scrap or rework; reduce cost; eliminate wasted time and material and profitable to the companies. However prior for Six Sigma application to construction require commitment from top management and readiness to accept changes in work process as well as adequate training for the staff.